Teachers training who teaches science: Contexts of diversity and decoloniality in theatrical acts (Revista Contexto & Educação, 2025)
In this article brings reflections and analyzes of a training research involving the theater, in approaching socially relevant themes, of a group of four undergraduate students, in development of the theme “Relations between Science, Society and Citizenship II”, investigating the contributions to the construction of narratives and subjectivities linked to racism, in the consideration of relations around a phenotypical characteristic such as “curly hair”. We turned to the decolonial perspective as an analytical lens, in the reading of the text of the scene produced and entitled “Thinking about STS and washing the hair: respect!”. The theater has the potential to contribute to decolonizing approaches to colonial effects. The theatrical narrative established the boundary between fiction and realities experienced by the students – real experiences and built subjectivities. The weight of differences and prejudices, in the face of racism, have moved the black population to express difficulties in self-acceptance, seeking alternatives to their appearance, such as straightening and dyeing hair, as presented in the theatrical plot, approximations to a white beauty standard or with traces of whiteness – manifestations of being coloniality. It is important that, in teacher education, the understanding of race as a cultural and not a natural entity is presented, privileging critical and creative pedagogical practices, mediators of social learning processes, in a destabilizing, questioning and problematizing perspective, like theater.
Keywords: Teacher training; Socially relevant issues; Racism; Theater